Prospect theory and two moment model: the firm under price uncertainty - Udo Broll; Martín Egozcue; Wing-Keung Wong (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
Within the prospect theory the paper examines production and hedging decisions of a competitive firm under price uncertainty. We consider the prospect theory for the firm's utility function in the two moment model known as (mu,sigma)-preference. In contrast to the literature our findings show that the production under uncertainty can be larger than in the certainty case. Furthermore, we demonstrate that although the futures markets are unbiased the firm is overhedging.
Keywords: D21; D41; D81; 330; Prospect theory; mean-variance model; price uncertainty